Accomplishing the Visions for Teacher Education Programs Advocated in the National Science Education Standards - (:unkn) unknown (My University, 2010)
The purpose of this study was to investigate the advantages of an approach to instruction using current problems and issues as curriculum organizers and illustrating how teaching must change to accomplish real learning. The study sample consisted of 41 preservice science teachers (13 males and 28 females) in a model science teacher education program. Both qualitative and quantitative research methods were used to determine success with science discipline-specific "Societal and Educational Applications" courses as one part of a total science teacher education program at a large Midwestern university. Students were involved with idea generation, consideration of multiple points of views, collaborative inquiries, and problem solving. All of these factors promoted grounded instruction using constructivist perspectives that situated science with actual experiences in the lives of students. © 2010 The Association for Science Teacher Education, USA.
Keywords: Applications; Constructivism; In-service; Pre-service; Science teaching and learning